Deterioro ambiental y percepción social en un área agropecuaria argentina - Fernández, Guillermina; Guerrero, Marcela; Jacinto, Guillermina; Nogar, Graciela; Posada, Marcelo; Valenzuela, Silvia (Revista de Ciencias Ambientales, 1996)
No disponible/Not available